An Uncommon Occurrence of Posterior Fossa Ependymoma in Elderly Patient: A Case Report - Taşkın Yurtseven; Mustafa Serdar Bölük; Hüseyin Biçeroğlu; Bilal Bahadır Akbulut (Düzce Tıp Fakültesi Dergisi)
Cerebellar ependymomas are rare neoplasms, even more so in elderly patients. In this case report, a 75-year-old male patient admitted with a one-year history of progressive general decline, urinary retention, left-sided weakness, memory loss, and insomnia was presented. Physical examination revealed left-sided hemiparesis and mild confusion. Cranial magnetic resonance imaging (MRI) showed a heterogeneously enhancing lesion measuring 22x15x20 mm originating from the fourth ventricle, with signs of hydrocephalus. The patient underwent tumor resection and placement of a ventriculoperitoneal (VP) shunt to address hydrocephalus. Postoperative MRI revealed no residual tumor, and the patient experienced gradual clinical improvement. Hemiparesis showed partial recovery, the overall condition stabilized, and he was subsequently discharged. Pathological examination confirmed a diagnosis of World Health Organization (WHO) grade II ependymoma. The patient is currently on a three-month follow-up.